Standardization Of Reverse Coffee At Restaurant Putuih Basambuang Malalak - Oktarican, Kasridho; Kasmita, Kasmita (Universitas Negeri Padang, 2023)
This research aims to study the method of making tatungkuik coffee at the Putuih Basambung Restaurant, Malalak District, Agam Regency, West Sumatra Province. The research activity was carried out in November 2022. The research method used was the survey method by direct observation of the process flow of tatungkuik coffee and interviews with the owner of tatungkuik coffee. The results of this study indicate that: 1) The materials used for roasting are as follows:53,3% Coffee beans, 16,4% black glutinous rice, 27,7% granulated sugar, and 2,6% cinnamon bark, 2) the temperature used during the roasting process is the initial temperature 72.6°C and continues to increase up to 107°C, 3) The amount of ingredients used to process or brew coffee is 13% coffee, 8,9%r sugar, 78,1% water with a temperature of 93.9 °C, 4) Tatungkuik coffee serving technique, technique or the way of serving Tatungkuik coffee is with one hand holding the glass and pushing it up and the left hand holding the saucer will swing it down and the coffee will face down and 5) The uniqueness of Tatungkuik coffee lies in the presentation of how to drink it, namely by blowing the glass meeting with the saucer using a straw and then the water comes out and coffee can be enjoyed.